Compensation and Employment Security - Graves, Spencer (My University, 1993)
Research by economists supports a couple of Japanese management practices that seem to have been underemphasized in many Total Quality implementation efforts in the US - lifetime employment and linking pay to the accomplishments of the team. This paper illustrates the value of these policies with a few examples from consulting experience, then describes research by economists that suggests that the effects noted in the examples are commonplace and not isolated incidents. The focus is primarily on the link between management policies and productivity and profitability; this should make the conclusions largely independent of an understanding of the role of quality in organizational performance.